Formulation of Antibacterial Mouthwash from Local Herbs: A Mini-Review (Journal of Biochemistry, Microbiology and Biotechnology, 2020)
Commercially available mouthwash formulations are often medicated and contain chemicals that may elicit adverse effects to the users. A mouthwash may be recommended for its efficacy in preventing dental caries and other oral conditions due to its antimicrobial, anti-inflammatory and analgesic properties. Therefore, it is essential to raise awareness in selecting for an appropriate mouthwash that is safe to be applied to the oral cavity and its natural microflora. The interest towards the incorporation of herbal ingredients in oral products has been increasing exponentially over the years. The main objective of this review is to highlight our consumption of food and herbal products, such as Aleppo oak, clove and turmeric, that contain medicinal properties and have the potential to be developed as key components in mouthwash formulations. Thus, reliance on the use of chemicals may lessen as they could have a negative impact to one’s oral health.
Keywords: Mouthwash; natural products; oral health; mouth cavities; plaques; caries